EFEKTIVITAS PELAKSANAAN PROGRAM PADANG PARIAMAN SEHAT DI KECAMATAN IV KOTO AUR MALINTANG - Ayu, Vina Putri; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Healthy Padang Pariaman Program is a program released by the Padang pariaman regent with the medical official, along with the regent rule no 15, 2015 about healthy Padang Pariaman. This healthy Padang Pariaman program was held by doing some visits to local midwives and the other medical officials and maximalize the use of mediacal facility and professionals which is used as services for the health of woman and infants in society. The problems which are found during this program are; the lack of attention by the medical officials to do some visits and medical check ups to the local society and the number of medical officials (midwives) in the PPS is not balance on handling the local people in IV Koto Aur Malintang regency which has many populations.According to the effectivity concept from Mahmudi which is used as the indicator in measuring the effectivity are input, process, output and outcome. The research method used is descriptive qualitative research. To get the informan, the researcher uses purposive sampling technique. The informan, in this research, are the chief of KIA Padang pariaman medical officials, the Coordinator of midwives in IV Koto Aur Malintang, Local midwives of IV Koto Aur Malintang, and the local people in IV Koto Aur Malintang.The finding of this research shows that the implementation of Healthy Padang Pariaman Prpgram in IV Koto Aur Malintang is not effective yet. this can be seen, first from the input, they are; the lack of human resource, the lack of facility to support the program, and the fund for the program is not fully managed. Second, the process, the socialization done by the government does not reach the target yet due to the information is not fully known by all local people. The third, the output, it can be seen that there are aims of the program that are not yet reached. The last but not least, the outcome, the benefit of the program is not fully felt by all local people.Key words : Effctivity, Healthy Padang Pariaman Program